High Toxocara cati prevalence in wild, free-ranging Eurasian lynx (Lynx lynx) in Finland, 1999-2015 - Virta, Miisa; Huitu, Otso; Heikkinen, Juha; Holmala, Katja; Jokelainen, Pikka (International Journal for Parasitology: Parasites and Wildlife, 2022)
In Finland, free-ranging Eurasian lynx (Lynx lynx) population has grown from 30 to 40 individuals to 2800 individuals since the species became partly protected in 1962. Changes in host population size are known to have an impact on host-parasite dynamics, and the Eurasian lynx population in Finland provides a unique opportunity for studying the potential effects of dramatic population increase and expansion of a solitary apex predator on their parasite prevalence and abundance. Toxocara cati is a zoonotic gastrointestinal parasite infecting domestic cats and wild felids worldwide. We studied T. cati infection prevalence and worm burden in 2756 Eurasian lynx individuals from Finland, covering the years 1999-2015. Toxocara cati worms that had been collected from intestinal contents were identified based on morphology. We performed regression analyses to investigate possible associations of age, sex, and host population density with T. cati infection. We found T. cati from 2324 (84.3%, 95% confidence interval 82.9-86.0) of the examined lynx. Each year, the infection prevalence was higher than 75% and not density dependent. The parasites were strongly aggregated, with older individuals harboring fewer T. cati than younger ones did. Old females aged 9-15 years had higher T. cati abundance than males of the same age group. Our results indicate that T. cati was a common and abundant parasite of Eurasian lynx throughout the study period, regardless of the changing population size and density. Peer reviewed